Using sectional blasting to improve the efficiency of making cut cavities in underground mine workings - Lozynskyi, Vasyl; Yussupov, Khalidilla; Rysbekov, Kanay; Rustemov, Serikbay; Bazaluk, Oleg (Frontiers in Earth Science, 2024)
The research concerns influence by the cut cavity making as well as optimum parameters to arrange both snubber and auxiliary blastholes on the improvement of drilling-and-blasting operations. The research methods include experimental and industrial activities to identify optimum depth of the first section snubber blastholes relative to the second section blastholes, and optimum parameters of the snubber blastholes while driving mine workings and ore breaking in stopes with different mine working sections and different strength of the broken rock mass using the technique of cut cavity formation. Experimental explosions, executed in a production environment, have proved efficiency of the proposed technique of sectional formation of a cut cavity, which helped perform 0.88 up to 0.97 increase in a blasthole use coefficient. It has been defined that depth of the first section boreholes should be identified taking into consideration length of the second section boreholes as well as the broken rock mass strength. The higher strength of the broken formation is, the larger the ratio between the first and the second section blasthole lengths is. Results of the experimental explosions have shown that depth of snubber blastholes of the first section varies from 0.5 and more of the second section boreholes depending upon the depth of the latter and the broken rock mass strength. If the broken formation is 12 (in terms of a Protodyakonov scale) and the second section blasthole increase is 1.6 up to 2.6 m then depth of the second section boreholes experiences 0.9 up to 1.54 m growth being 0.55-0.56 of the second section blasthole length. If strength of the broken formation is 18, and it coincides with length values of the second section then the first section length is varying from 0.9 to 1.75 m being 0.5-0.62 of the second section blasthole length. Application of the novel proposed procedure for a cut cavity formation will increase blasthole use coefficient and reduce the cost of drilling-and-blasting operations. Moreover, the procedure may also be practical for underground mine working driving as well as for ore breaking within stopes.